Direct Fibrinolytic Snake Venom Metalloproteinases Affecting Hemostasis: Structural, Biochemical Features and Therapeutic Potential - Eladio F. Sanchez; Renzo J. Flores-Ortiz; Valeria G. Alvarenga; Johannes A. Eble (Toxins, 2017)
Snake venom metalloproteinases (SVMPs) are predominant in viperid venoms, which provoke hemorrhage and affect hemostasis and thrombosis. P-I class enzymes consist only of a single metalloproteinase domain. Despite sharing high sequence homology, only some of them induce hemorrhage. They have direct fibrin(ogen)olytic activity. Their main biological substrate is fibrin(ogen), whose Aα-chain is degraded rapidly and independently of activation of plasminogen. It is important to understand their biochemical and physiological mechanisms, as well as their applications, to study the etiology of some human diseases and to identify sites of potential intervention. As compared to all current antiplatelet therapies to treat cardiovascular events, the SVMPs have outstanding biochemical attributes: (a) they are insensitive to plasma serine proteinase inhibitors; (b) they have the potential to avoid bleeding risk; (c) mechanistically, they are inactivated/cleared by α2-macroglobulin that limits their range of action in circulation; and (d) few of them also impair platelet aggregation that represent an important target for therapeutic intervention. This review will briefly highlight the structure–function relationships of these few direct-acting fibrinolytic agents, including, barnettlysin-I, isolated from Bothrops barnetti venom, that could be considered as potential agent to treat major thrombotic disorders. Some of their pharmacological advantages are compared with plasmin.